The effect of damping components on the interfacial dynamics and tribological behavior of high-speed train brakes. (July 2021) - Wu, Y.K.; Xu, J.W.; Wang, X.C.; Chen, W.; Lu, C.; Mo, J.L.
Abstract: Improving the interfacial dynamics and tribological behavior of high-speed braking systems are important for train safety. The effects of different damping components on the interfacial dynamic response and tribological properties of a braking system are presented in this study. Firstly, four kinds of damping components made of fluororubber, polytetrafluoroethylene (PTFE), Mn-Cu alloy and Mn-Cu damping alloy materials are introduced into the braking system, respectively. Drag-type brake tests are performed with a self-designed high-speed railway brake dynamometer. The vibration, noise signal, thermal distribution at the interface, and wear behavior under different configurations of the braking systems are analyzed. In addition, numerical simulations are conducted to provide explanations for the experimental results. The results indicate that the vibration response, noise characteristic, and interface contact state are affected by the deformation behavior and damping properties of the damping components. With the help of damping components, the friction-induced vibration and noise (FIVN) is reduced and the interfacial contact state is improved. It is found that the fluororubber component plays a significant role in improving the interface contact state of the braking system. While the Mn-Cu damping component has an excellent performance in FIVN suppression. Finally, composite damping components of fluororubber and Mn-Cu damping alloy with different thickness ratios are introduced into the braking system to analyze the performance of composite damping components on the dynamical and tribological behavior of the braking systems.